Visitor awareness of brown bear (Ursus arctos) human-food conditioning in Bieszczady and Tatra National Parks (Carpathians, Poland) - Spalona, Anna (Biological Letters, 2013)
This paper investigates the awareness of visitors to Bieszczady National Park (BNP) and Tatra National Park (TNP) of human influence on brown bears (Ursus arctos Linnaeus, 1758), i.e. what causes human-habituated bears to become food-conditioned. In the parks studied, 928 questionnaires were collected in July and August 2007. The survey was supplemented with data on the amount of garbage collected in both parks by municipal services in 2007. Respondents in BPN displayed significantly greater knowledge about the causes of human-food conditioning of bears than respondents in TNP (64.2% and 52.7%, respectively, had more than the average of 3.54 correct answers per 5 questions in the questionnaire). As many as 60.1% of visitors in both parks incorrectly associated human-food conditioning with a lack of natural food and 34.4% withan excessive number of bears. Most respondents did not realise that to prevent human-bear conflict, decisive actions must be taken towards every food conditioned bear observed in the free-living population. Unlike in BNP, in TNP there is a large amount of rubbish left by visitors along trails. In 2007, municipal services collected in both parks a similar amount of garbageper 1000 visitors (0.39 m3 and 0.37 m3 in BNP and TNP, respectively) but the annual number of visitors is nearly 8‑fold lower inBNP than in TNP. In BNP, only visitors put rubbish in containers, while in TNP, additional 6 cleaning companies are employed to collect rubbish thrown by visitors along trails. In contrast to TNP, however, in BNP there are no bear-proof containers. Both parks need to prevent the access of bears to rubbish. It is also advisable to initiate an effective information campaign among visitors about prevention of human-food conditioning of bears.